Effectiveness of Taijiquan in treating insomnia: A systematic review and meta-analysis of randomized controlled studies - Han, Dongmiao; Cheng, Jinling; Qu, Jiayang; Wen, Xin; Liu, Xuejin; Chen, Yanfeng; Wen, Youliang; Liu, Zicai; Liu, Huiyu; Huang, Ying (Frontiers in Psychiatry, 2022)
Background: It is known that adequate sleep is very important for human wellbeing, affecting people's work and life, insomnia will seriously damage our daily life. There is no recognized non-drug treatment. Studies have found that Taijiquan has a positive effect on insomnia patients. This systematic review and meta-analysis will evaluate the effect of Taijiquan on insomnia. Methods: To find all randomized controlled trials exploring the effects of Taijiquan on insomnia patients in Chinese and English, eight databases (Pubmed, Embase, Cochrane library, Web of Science, CNKI, CBM, VIP, and Wanfang Data) were searched. The retrieval time is from database construction to October 2021. Searches were conducted in both English and Chinese language. A meta-analysis by mean difference (MD) and 95% confidence interval (CI) was performed with RevMan 5.3. The risk of bias for each study was accounted for according to the Cochrane Handbook. Our primary outcome was Pittsburg Sleep Quality Index. We explored sources of heterogeneity by comparing effect sizes across different types of etiology, country, control group, and intervention type. The protocol was pre-registered with PROSPERO, CRD42021284511. Results： Twenty-one RCTs published between 2004 and 2021 with 2022 participants were included in this study. Twenty-one randomized controlled studies showed that Tai Chi significantly improved PSQI scores in patients with cancer, muscle fibrosis, and sub-health insomnia [MD= -1.16, 95% CI (-1.62, -0.71), P＜0.01]; There is insufficient evidence of improvement in patients with cerebrovascular disease [MD= -0.54, 95% CI (-1.58, 0.51), P=0.31]; 8-form, 10-form or 24-form Yang's Taijiquan had the same effect in improving PSQI[MD= -1.33, 95% CI (-1.85, -0.81), P＜0.01]. When there is no treatment, exercise, exercise and health education as the control, taijiquan has a significant effect on insomnia treatment, and there is no difference in efficacy compared with cognitive behavioral therapy and health education (usual care) alone. Conclusions: The results of the study showed that Taijiquan significantly improved sleep quality in healthy adults and patients with chronic diseases, which suggests that Taijiquan may be considered as an alternative behavioral therapy in the treatment of insomnia. In the future, more high-quality, well-controlled randomized trials are needed to better inform clinical decisions.